2022
DOI: 10.1108/wwop-12-2021-0061
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in patients with heart failure: contributing factors, consequences and coping mechanisms: a review of the literature

Abstract: Purpose The purpose of this study is to integrate evidence on contributing factors, consequences, in addition to coping mechanisms of depression and anxiety in patients with heart failure. Design/methodology/approach An integrative review was conducted by searching three main electronic databases: Web of Sciences, MEDLINE and Science Direct. Twenty-four studies met the inclusion criteria and were included in the final review process. Findings The review identified the most common contributing factors, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Depression also has serious repercussions on its victims. Persistent depression may cause its victims to develop other health issues like heart disease (Charlson et al ., 2011; Abu Sumaqa and Hayajneh, 2022). Further, the number of cases related to depression increased recently due to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Depression also has serious repercussions on its victims. Persistent depression may cause its victims to develop other health issues like heart disease (Charlson et al ., 2011; Abu Sumaqa and Hayajneh, 2022). Further, the number of cases related to depression increased recently due to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several previous studies found that the psychological aspects of patients with HF have been associated with poor self-care maintenance, self-care management, and confidence ( Biddle et al, 2020 ; Chang et al, 2017 ; Chuang et al, 2019 ; Freedland et al, 2021 ; Liljeroos et al, 2020 ; Jaafar et al, 2019 ; Mueller-Tasch et al, 2018 ; Tegegn et al, 2021 ; Tovar et al, 2015 ). Many prior studies showed that the psychological aspects are associated with poor quality of life ( An et al, 2022 ; Alemoush et al, 2021 ; Abu Sumaqa & Hayajneh, 2022 ; Hyarat et al, 2019 ; Moradi et al, 2020 ; Uchmanowicz & Gobbens, 2015; van den Berge et al, 2022 ). Few qualitative studies have addressed the consequence of psychological distress in patients with HF.…”
Section: Introductionmentioning
confidence: 99%